Meta-analysis of the Studies on the Factors Affecting Sports and Physical Activity of the Older Adults in Iran - Leila Esmi; Reza Nikbakhsh; Taiebeh Zargar; Hassan Ghasmalipour (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives The existence of a large number of studies on exercise and physical activities of the elderly, whose results are somewhat contradictory, has made planning and policy-making for this area difficult. It is necessary to combine and integrate the results of these studies. Therefore, the current study aims to conduct a meta-analysis of the studies on factors affecting exercise and physical activity of the elderly in Iran. Methods & Materials This is a meta-analysis and systematic review study of descriptive studies (survey or correlational) conducted in Iran assessing the factors affecting the exercise and physical activity of older adults in Iran from 2011 to 2021, and were available through searching in the databases. Based on the inclusion and exclusion criteria, 17 articles were finally selected for the review. To analyze the studies, the effect size for each study, the mixed effect size with two fixed and random effects models, funnel plot, sensitivity analysis, homogeneity test, I2 statistic and the failsafe statistic (FS-N) were used. The type of effect size index was the r index, which was calculated in CMA software, version 2. Results The mixed effect size was r=0.528 for the random-effects model and r=0.532 for the fixed-effects model. Among 73 effect sizes, 15 had small sizes, 37 had moderate sizes, and 21 had big sizes. It was found that sociocultural factors had the biggest effect sizes (r=0.622) followed by individual factors (r=0.591), motivation (r=0.573), environmental factors (r=0.572), economic factors (r=0.478), and interpersonal factors (r=0.431). Conclusion Exercise and physical activity of the elderly in Iran is influenced by several factors and simply emphasizing a specific factor cannot help increase their activities. However, it is recommended to consider sociocultural, individual, motivational, environmental, economic, and interpersonal factors more than other factors that affect exercise and physical activity of the elderly.